MIRERC 035/2025 FACTORS INFLUENCING HPV VACCINATION UPTAKE AMONG CAREGIVERS OF ADOLESCENT GIRLS IN THE PASTORALIST COMMUNITY OF GARBATULLA, ISIOLO COUNTY, KENYA. - KUBI, SABLA GALGALO; Dr. MaryJoy Kaimuri; Dr. Jane Rutto, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
ABSTRACT The prevalence of infection with high-risk human papilloma virus among Kenyans and globally is rising and posing a public health concern. This has begun to reflect on the steady increases in cervical cancer cases in the country. Currently, cervical cancer is the second most common cancer among women in Kenya, after breast cancer. Two major strategies to control the rise of HPV infections and cervical cancer is vaccination and the regular screening of young women. The World Health Organization has recommended the vaccination of all girls between the ages of 9-14 years before their coitarche. In 2019, Kenya launched national vaccination drive targeting girls 10 years old and which was integrated into the routine immunization schedule. However, coverage remain low across the country particularly among the hard-to-reach populations such as the nomadic pastoralist communities. This study aims to investigate the factors influencing HPV vaccination uptake among age-eligible girls in the pastoralist community of Garbatulla, Isiolo County. The study will employ a cross-sectional mixed-methods design on sample size of 347 caregivers with adolescent girls aged 15-18 years. Quantitative data will be collected using structured questionnaires administered by the research team while qualitative data will be collected with aid of Focus Group Discussion guides and Key Informant Interview guides. Pretesting will be conducted on 10% of the sample size in Sericho Ward. SPSS version 27 will be utilized to facilitate the analysis. Descriptive statistics will be presented using frequencies and percentages for categorical data and means and medians for continuous data. chi-square test will be used to test associations between categorical variables while and binary logistics regression analysis will be utilized to investigate the predictor variables for vaccinate uptakes among the participant adolescents while thematic content analysis will be used for qualitative data. Findings will be presented using tables and charts. Ethical approval will be sought from Meru University Ethical Review Committee. Research approval will be sought from the Meru University Graduate School, while a research permit will be sought from the National Commission for Science Technology and Innovation (NACOSTI). Potential respondents will be enrolled to participate based on their informed consent.